Self-Efficacy, Empowerment, Anxiety And Sense Of Coherence In Nurse, México - Escobar-Castellanos, Blanca; López González, Juan Alberto; Padilla Languré, Marcela; Cuén Tánori, Francisco Andrés (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Nursing work situations have developed in an environment of uncertainty, affecting their mental health. A descriptive correlational study was carried out that allowed determining the association of self-efficacy, empowerment, and anxiety with a sense of coherence in 174 nurses from health institutions in Sonora, Mexico. 50.9% had high self-efficacy, 54.3% high empowerment, 52.6% low anxiety and 50.3% low sense of coherence. There was a significant statistical association in self-efficacy, empowerment, anxiety with a sense of coherence with p=0.01. It is essential to establish strategies to preserve mental health in the nursing staff of health institutions.